2019
DOI: 10.21273/hortsci13571-18
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Irrigation Improves Turfgrass Safety to Postemergence Herbicides

Abstract: Summer annual grassy weeds such as goosegrass (Eleusine indica L. Gaertn.) continue to be problematic to control selectively with postemergence (POST) herbicides within turfgrass stands. In recent years, reduced performance by certain herbicides (e.g., foramsulfuron), cancellation of goosegrass-specific herbicides (e.g., diclofop-methyl), and cancellation and/or severe use reductions of other herbicides [e.g., monosodium methanearsonate (MSMA)] have limited the options for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…Topramezone at 10 g ha −1 plus metribuzin at 100 g ha −1 was observed to control E. indica 90% to 100% (Lindsey et al 2020). Kerr et al (2019aKerr et al ( , 2019b sought to reduce bermudagrass response to topramezone at 12 g ha −1 with or without metribuzin at 420 g ha −1 by immediate post-treatment irrigation. Irrigation at 0.6 cm within 1 min of spray application did not reduce initial bermudagrass injury but slightly improved recovery as assessed at 4 WAIT in South Carolina and Alabama (Kerr et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Topramezone at 10 g ha −1 plus metribuzin at 100 g ha −1 was observed to control E. indica 90% to 100% (Lindsey et al 2020). Kerr et al (2019aKerr et al ( , 2019b sought to reduce bermudagrass response to topramezone at 12 g ha −1 with or without metribuzin at 420 g ha −1 by immediate post-treatment irrigation. Irrigation at 0.6 cm within 1 min of spray application did not reduce initial bermudagrass injury but slightly improved recovery as assessed at 4 WAIT in South Carolina and Alabama (Kerr et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…However, irrigating following application compromised topramezone efficacy on goosegrass, resulting in 30% less control compared to nonirrigated plots. Kerr et al (2019a) observed a similar reduction in turfgrass injury when irrigating following application of topramezone (12.3 g ha -1 ), carfentrazone þ 2,4-D þ dicamba þ MCPP (500 g ha -1 ), and topramezone (12.3 g ha…”
Section: Introductionmentioning
confidence: 62%
“…Goosegrass is a pervasive weed of warm-season turfgrass. Many herbicides used for POST goosegrass control cause unacceptable injury to warm-season turfgrasses such as bermudagrass (Busey 2004;Cox et al 2017;Johnson 1980;Kerr et al 2019aKerr et al , 2019bMcCarty 1991;Nishimoto and Murdoch 1999). In turfgrass systems, loss of herbicides such as diclofop-methyl and monosodium methanearsonate has further limited options available for POST goosegrass control (Cox et al 2017;Kerr et al 2019aKerr et al , 2019bLeibhart et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest dose of sewage sludge (1,428 g m -2 ) positively influenced the Normalized Difference Vegetation Index (NDVI), with an average of 0.53 (Figure 2A), 39.41% higher compared to control treatment (0 g m -2 ). This index can indicate when the lawn is exposed to stresses such as trampling/compaction, utilization, and water deficit (Kerr et al, 2019;Straw et al, 2020). NDVI can be used as an alternative to evaluate the DCGI in the turfgrass (Caturegli et al, 2020).…”
Section: Resultsmentioning
confidence: 99%